Crystal growth, structural phase transitions and optical gap evolution of FAPb(Br1-x Cl x )3 hybrid perovskites (FA: formamidinium ion, CH(NH2)2 +) - Carlos A. López; Oscar Fabelo; Carmen Abia; María T. Fernández-Diaz; José A. Alonso (Discover Nano)
Abstract Chemically tuned organic–inorganic hybrid halide perovskites based on bromide and chloride anions CH(NH2)2Pb(Br1−x Cl x )3 (CH(NH2)2 +: formamidinium ion, FA) have been crystallized and investigated by neutron powder diffraction (NPD), single crystal X-ray diffraction (SCXRD), scanning electron microscopy (SEM) and UV–vis spectroscopy. FAPbBr3 and FAPbCl3 experience successive phase transitions upon cooling, lowering the symmetry from cubic to orthorhombic phases; however, these transitions are not observed for the mixed halide phases, probably due to compositional disorder. The band-gap engineering brought about by the chemical doping of FAPb (Br1-x Cl x )3 perovskites (x = 0.0, 0.33, 0.5, 0.66 and 1.0) can be controllably tuned: the gap progressively increases with the concentration of Cl− ions from 2.17 to 2.91 eV at room temperature, presenting a nonlinear behavior. This study provides an improved understanding of the structural and optical properties of these appealing hybrid perovskites.